(untitled) (Sains Humanika, 2012)
The Arabic course at Universiti Teknologi MARA (UiTM) Malaysia is an elective offered to first degree students. The objective of this study is to identify the use of effort regulation strategy among students in learning oral Arabic skills at UiTM. It is a mixed method of quantitative andÂ qualitative study using a self-regulated learning questionnaire adapted from The Motivated Strategies for Learning Questionnaire (MSLQ) and interviews. For quantitative data, the stratified random sampling technique was used involving 445 samples, while for qualitative data, 21 interviews were engaged, comprising 13 interviews with students and 8 with lecturers. The study found that the use of this strategy is moderate. Among factors that influence the use of this strategy are studentsâ€™ learning orientation and types of learning activities used in learning. This study suggests some improvements in oral Arabic learning at UiTM such as nurturing intrinsic learning orientation among students as well as engaging more collaborative and autonomous grouping activities.